THE ROLE OF SPIRITUALITY AND RELIGION IN PSYCHOLOGICAL AND PHYSICAL HEALTH OF WOMEN IN NIGERIA - Adaobi Jennifer Iloakasia (INJOSEDU: International Journal of Social and Education, 2025)
For many women in Nigeria, spirituality and religion are part of daily life and well-being. They bring comfort, ease stress, and encourage healthy living. In places where healthcare is not readily available, faith often fills the gap—making it a powerful source of support for both mind and body. This study was therefore framed within the Health Belief Model (HBM) and Pargament's Theory of Religious Coping to explored the role of spirituality and religion in the psychological and physical health of women in Nigeria. A descriptive survey design was used, and data were gathered through a self-developed online questionnaire that focused on four key areas: spirituality, religious involvement, psychological health, and physical health. The instrument was reviewed and validated by three experts in Educational Psychology, Guidance and Counselling, and Measurement and Evaluation to ensure its clarity and relevance. Its reliability was confirmed using Cronbach’s alpha, with a reliability coefficient of 0.77, 0.81, 0.92 and 0.88 respectively for spirituality, religious involvement, psychological health, and physical health clusters, indicating a high level of internal consistency. The questionnaire was distributed over a two-week period through women-focused social media groups, and a total of 400 completed responses were received. The data were then analyzed using descriptive statistics and correlation analysis. The findings showed that out of 400 women, most were single (47.3%), married (27.0%), widowed (20.3%), or divorced (5.5%). The mean scores for spirituality (3.17), religious involvement (3.19), psychological health (3.02), and physical health (3.08) were high. Strong positive correlations were found between all variables, especially between religious involvement and physical health (r = 0.822). ANOVA results confirmed that spirituality significantly predicts psychological (F = 122.28) and physical health (F = 316.46), while including religious involvement further strengthened these effects (F = 139.38, 877.78). Regression models showed that both spirituality and religious involvement positively influence women's health outcomes, with religious involvement having a stronger impact on physical health. Based on these results, the study recommended that health and wellness programs aimed at women in Nigeria should take spiritual and religious factors into account, especially within culturally sensitive frameworks.